The maintenance of our present money system - Peterson, W.O. (My University, 1897)
Introduction: At this time an introduction to a subject of this kind is probably unnecessary. It seems that every American citizen is wide-awake on the money question; yet where one hundred are discussing what our financial system should be there is hardly one that knows what it really is. Of what does our present money system consist? In brief it has the metal gold for a foundation; in other words gold is the standard of value. On this metal as a foundation we build our financial superstructure of silver, copper, nickel and paper. Gold, silver and paper currency are our legal tender for the payment all debts or obligations, both public and private. Among the advantages of our present monetary system are: 1. Its stability. I believe this quality should be the first requisite of any money system. For if the money declines in value prices must rise and if it rises in value prices must fall. To illustrate: Money is dearer now than it was about twenty-five years ago. Actual facts show us that prices are lower now than they were then. Then one hundred pounds of flour cost from six to eight dollars; now the same amount can be had for about one-third that sum.
Citation: Peterson, W.O. The maintenance of our present money system. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Economics; Money; Currency; Gold standard; Theses; Manuscripts (documents)